Metabolomics Unveiled the Accumulation Characteristics of Taste Compounds During the Development and Maturation of Litchi Fruit - Nonghui Jiang; Wei Liu; Zhidan Xiao; Xu Xiang; Yun Zhong (Foods)
Litchi is one of the ancient fruits that originated in China, renowned for its high nutrition and rich flavor, and Xianjinfeng (XJF) stands as one of the most notable varieties in terms of its flavor. Investigating the metabolic changes in taste compounds during fruit development offers deeper insights into the formation patterns of fruit quality. In this study, we conducted extensive metabonomic research on the accumulation patterns of taste compounds (carbohydrates, organic acids, and amino acids) across three developmental stages of XJF litchi. A total of 238 taste metabolites were detected. Cluster analysis and PCA revealed significant changes in metabolite composition and content across different stages, closely correlating with the developmental phase. The abundance of total taste metabolites in stage S1 was notably lower than stages S2 and S3. The total abundance of sugar continued to rise, yet monosaccharides and disaccharides exhibited distinct behaviors, highlighting the characteristic accumulation of reducing sugars. Most organic acids demonstrated a notable downward trend, whereas the abundance of most essential and flavor-contributing amino acids showed an upward trend. The number of DAMs across the three stages followed the trend of S1 vs. S3 > S1 vs. S2 > S2 vs. S3. KEGG functional annotation and enrichment revealed that amino acid biosynthesis, D-amino acid metabolism, 2-oxocarboxylic acid metabolism, glyoxylate and dicarboxylate metabolism, the pentose phosphate pathway, the tricarboxylic acid cycle, and carbon metabolism were the most significantly enriched primary metabolic pathways. More differential metabolites and metabolic pathways indicated that the critical stage from the green fruit stage to the color transition stage laid a solid foundation for litchi flavor. This experiment will offer valuable references for cultivation, breeding, processing, and consumption.